«Tables as metaphors. Europe in the World and cultural diplomacy» - Conde, I. (International «Conference Europe as Global Actor» hosted by the Center for International Studies (CEI-IUL) ISCTE – IUL, 24-25 maio 2018, 2018)
“Tables as metaphors” is the visual frieze to open this paper about the current cultural strand in EU global statements and strategy, so to say Europe in the world and the role of cultural diplomacy. A notion with nuances, from “soft power” to the dialogic frame of cultural co-operation, for which the tables symbolize meeting points; all a range of expectations, exchanges, confrontations, negociations, resolutions or failures in the relation intra/inter countries and geo-political blocs. Using images to spare in words, some tables-metaphors in art installations show distinct views vis-à-vis the international dis/order and the sinuous diplomacy. From confident or expectant to critical and dystopian, they are tables created by Michelangelo Pistoletto, Antoni Muntadas, Mark Clare, Asier Mendizábal and so, closing the circle, by top artists with chance to be invited to perform the own cultural diplomacy in the usual events (e.g. exhibitions promoted by trans/national institutions), be it a performance even with some deceptive tables. Beyond issues of semantics around cultural diplomacy, for the European Union the main is to re-draw the agenda as announced in the report to summarize: «Preparatory action ‘Culture in EU External Relations’ engaging the world: towards global cultural citizenship» (2014). To place it in wider outlook the paper also gives a portrait the EU’s cultural position in the world by a selection of indicators concerning the international cultural trade; the web of cultural institutes in Europe for external action; and some items in views from outside the EU. Namely, data from the last Eurobarometer (2017) about the subject with a sample of views in 11 countries, including European cases (Norway and Switzerland, both outside EU28) and “borders” (Russia, Turkey), the Western axis (Australia, Canada, United States of America) and Asia (China, Japan, India) as well as the voice of Brazil in Latin America.